Regulation of Immune Reactivity by Intercellular Transfer - Moser, Muriel; Dhainaut, Maxime (Frontiers in Immunology, 2014)
It was recently proposed that T lymphocytes, which closely interact with APCs, can extract surface molecules from the presenting cells when they dissociate. These observations question the classical view of discrete interactions between phenotypically defined cell populations. In this review, we summarize some reports suggesting that membrane exchange at the immune synapse can be a vector for intercellular communication and envisage some consequences on the biology of T cells.